The Bases of the Social Consensus in Holy Quran and in Iran Constitution Law (Global Journal of Human-Social Science, 2014)
In the present research the bases of social consensus in Holy Quran and the Constitution law have been studied. In every society social consensus has been affectedby various factors, but certainly the ideological, legal and political bases in every society have an important role in it. This study has emphasized on the teachings of Holy Qur'an & the Constitution law. It is a qualitative content analysis with semantic, box and cumulative classifications, the unit of content analysis and two corpuses for analysis (Holy Qur'an and The Constitution Law). The results show that the teachings of Holy Qur'an from the ideological, social and political point of view have formed the basis of social consensus that from the political legal point of view has been realized in the Constitution Law, too. It forms the base of convergence behaviors in the society. It has been realized in value, cognitive, functional, rank and conventional dimensions in the Constitution Law.
Keywords: social consensus-holy qur'an-constitution law